Automatic Agriculture Crop Yield Production Maintenance System Based On Remote Monitoring Techniques In Cloud Environment - et. al., Mrs. Alka Kulkarni, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In agriculture, productivity can be measured in the percentage of a crop grown and the ratios of the seed are the factors for calculating agricultural productivity. With a change in climate situation to increase pollution and increased world population, it becomes a serious concern to secure world food resources. The proposed system is essentially developed for suggesting the acceptable crop which will be cultivated within the region by considering various parameters like temperature, moisture humidity levels. It is especially designed for farmers also as for soil investigation centers where the soil is given as input for fetching the soil properties using different sensors. We are getting to develop an android application in order that interface is going to be easily accessible and user friendly for the persons with non-technical background. The most objective of the paper is to supply crop yielding process which is satisfactory for cultivation based on the climate changes using the sensor and disease prediction providing fertilizer list for the previous using K means clustering algorithm.